The Microbiological Characteristics of the Microwave-treated Samples and the Convection-heat-treated Samples Shows No Deviation in Case of Surface Water Treatment - Barczi, András; Lippai, Anett (Journal of Central European Green Innovation, 2023)
Applying the comparative method, we applied microwave and convective heat treatment on water samples from surface water. By determining microbiological parameters, we searched for detectable deviations in any parameter beyond the effect of heat treatments. The effect of heat treatments was detectable in all cases, but the thermal effects were the same regardless of the method of heat treatment, at a frequency of 2450MHz and a power of 900W. We observed microbiological characteristics that may not only change with thermal effects. Highlighting that, our research is based on the exact same treatment time and applied temperature. The microbiological characteristics of the microwave-heat-treated samples showed no deviation as those of the convectively heat-treated samples; this was checked by two-sample t-test at a significance level of p
Keywords: microwave heat treatment; microbiological parameters; TBC; heat; water